POTENCY AND STRATEGY OF BIOENERGY DEVELOPMENT FOR CLIMATE CHANGE MITIGATION IN BANDUNG BASIN METROPOLITAN AREA (CASE STUDY: CALLIANDRA TREE) - Senoputri, Mega
Global consumption of energy escalates rapidly over recent years and known to be one of the main contributors of Greenhouse Gasses (GHG) that caused climate change. Bioenergy utilization is seen as one kind of solution to reduce GHG emission from energy sector. However, potential land competition with food crops, as well as the possibility of additional emission from its production and distribution process, are considered as a problem in bioenergy development. This study aims to analyzes the potency and strategy of bioenergy development for climate change mitigation in Bandung Basin Metropolitan Area. Marginal land in metropolitan area is expected to be potential for bioenergy cultivation based on hypothesis that cultivation of forest-based energy crops in marginal land will have minimum risk of land competition and bioenergy development in urban area will reduce the amount of GHG emission from its production process. This study focused on Bandung Basin Metropolitan Area (BBMA). Bioenergy used in this study is wood pellet from Kaliandra tree (Calliandra calothyrsus). The result of spatial analysis shows that most of marginal land in BBMA is potential to be utilized for Kaliandra cultivation. Maximum utilization of this potency can be done by using marginal land classified as “Agriculture Cultivation Area” (B4), “Production Forest” (B6), and Protected Forest (L1) with limited ulitization. Area with highes possibility to be used as energy forest is two sites in Kab. Bandung Barat and Kab. Bandung which are included into the forest rehabilitation area plan. GHG emission from the production of electricity from Kaliandra wood in BBMA is analyzed using Life Cycle Assessment (LCA). The result of LCA analysis indicated that the amount of carbon gasses absorbed during the production ofiv electricity from Kaliandra wood is higher than the amount of GHG emitted during the same process if being operated for more than 8,08 years. The use of Biomass Power Plants from Kaliandra wood will support mitigation action in Regional Action Plan for GHG Emission Reduction (RAD GRK) of West Java Province by increasing the potential reduction of GHG emission from energy supply and usage sub sector from 7,99% to 8,62%. Strategies should be done to support the development of forest-based bioenergy in marginal land of urban area are mainstreaming climate change mitigation into national and local energy policies, formulating financial instruments to stimulate transition from fossil-based energy to bio-based energy, as well as optimizing local government’s role on providing local energy with low GHG emission and high economical benefits to local people